Development of a simple HPLC-UV method for determination of GFR by serum iohexol clearance - van Der Westhuizen, Diederick J (Department of Clinical Laboratory Sciences, 2023)
The glomerular filtration rate (GFR) is considered the best indicator of kidney function. Iohexol, a contrast agent, is currently considered to be a reference marker since it meets all the requirements of an ideal GFR marker. The aim of this study was to develop and validate a method for iohexol measurement using high performance liquid chromatography with ultraviolet detection (HPLCUV). The method developed includes a mobile phase with water and acetonitrile with a gradient of 5%-30% organic, a C18 analytical column (100 × 4.6 mm, 2.7 µm particle size) at a temperature of 40 °C and a flow rate of 0.5 ml/min. Serum samples were deproteinized by addition of perchloric acid (5%). The assay met the sensitivity cut-off with a mean signal-to-noise ratio of 17.2 at a level of 10 µg/mL iohexol. Mean recovery was 103.7% (CV=4.4%). The dilution experiment allowed for 5-times dilution up to iohexol levels of 500 µg/mL with an accuracy of 103.1% (CV=1.3%) For selectivity, no interfering endogenous compounds at the retention time of iohexol were observed. The matrix effect experiment showed a clinically acceptable variation at all concentration levels with a CV of the slopes of 2.7%. Stability of the stock solution was proven for at least 9 months at -80°C. Sample post-extraction stability was adequate at 84 hours. Interference testing yielded between -7% and -12% difference at 2% haemolysis and -9% to -13% difference at 10% lipaemia. With regards to these findings, this method is simple, specific, linear, precise and robust, which allows its application for the measurement of GFR in serum.